2012
DOI: 10.1590/s1983-14472012000100023
|View full text |Cite
|
Sign up to set email alerts
|

Sistematização da assistência de enfermagem a pacientes oncológicos: uma revisão integrativa da literatura

Abstract: This is an integrative review that aimed to present the knowledge produced on the process standards of nursing care (SAE) through the Nursing Process (NP) for cancer patients. Data was collected from September to October, 2010 in the electronic databases Scopus, Nursing and Allied Health Literature (CINAHL) and Scientific and Technical Literature of Latin America and the Caribbean (LILACS). Five articles were found. The results show that the majority of studies are descriptive and exploratory. Routinely, NP ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
15

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
0
5
0
15
Order By: Relevance
“…• When pain is not systematically evaluated, it may be underestimated and important factors may be missed. Inadequate pain evaluation and unawareness of available strategies for its control are factors which may impair the handling of this symptom 8,12,18,21 ; • Holistic approach: Four studies have observed nursing attention to meet cancer patients needs in all their aspects (physical, emotional, social and spiritual), where nurses should tirelessly act to eliminate or minimize patients anxieties and desires; however, to do so, it is necessary for the professional to have a unique nursing profession profile, constantly looking for technical-scientific knowledge and acting in an interpersonal and humanized way, because nursing professionals need to interpret the subjectivity of every patient to reach the desired goal which is their quality of life 19 ;…”
Section: Axis 2 -Nursing and Cancer Pain Patientsmentioning
confidence: 99%
“…• When pain is not systematically evaluated, it may be underestimated and important factors may be missed. Inadequate pain evaluation and unawareness of available strategies for its control are factors which may impair the handling of this symptom 8,12,18,21 ; • Holistic approach: Four studies have observed nursing attention to meet cancer patients needs in all their aspects (physical, emotional, social and spiritual), where nurses should tirelessly act to eliminate or minimize patients anxieties and desires; however, to do so, it is necessary for the professional to have a unique nursing profession profile, constantly looking for technical-scientific knowledge and acting in an interpersonal and humanized way, because nursing professionals need to interpret the subjectivity of every patient to reach the desired goal which is their quality of life 19 ;…”
Section: Axis 2 -Nursing and Cancer Pain Patientsmentioning
confidence: 99%
“…This search method also shows knowledge gaps that need to be fulfilled with new studies. [11] The current study comprises the following stages: development of guiding questions such as "How are simulations used in emergency nursing education? What are the types of adopted simulations?…”
Section: Methodsmentioning
confidence: 99%
“…Dentre as comorbidades estudadas em transplante sabe-se que o custo com o tratamento de infecções onera o custo total do procedimento, além de requerer mais horas de enfermagem devido à complexidade do paciente infectado. 7 Para o ano de Observou-se a escassez de trabalhos desenvolvidos na área de avaliação econômica por enfermeiros no Brasil. Os Estados Unidos foram o país em que mais se encontraram trabalhos de análise econômica desenvolvidos por enfermeiros.…”
Section: Comounclassified